Complementary and Supplementary Fit: A Theoretical and Empirical Integration. - Cable, Daniel M.; Edwards, Jeffrey R. (Journal of Applied Psychology, 2004)
Complementary and supplementary fit represent 2 distinct traditions within the person-environment fit paradigm. However, these traditions have progressed in parallel but separate streams. This article articulates the theoretical underpinnings of the 2 traditions, using psychological need fulfillment and value congruence as prototypes of each tradition. Using a sample of 963 adult employees ranging from laborers to executives, the authors test 3 alternative conceptual models that examine the complementary and supplementary traditions. Results show that an integrative model dominates the other two, such that both traditions simultaneously predict outcomes in different ways.